COEXISTENCE OF MULTIPLE GENE VARIANTS IN SOME PATIENTS WITH ERYTHROCYTOSES - Andrea Benetti; Irene Bertozzi, PhD, MD; Giulio Ceolotto; Irene Cortella; Daniela Regazzo; Giacomo Biagetti; Elisabetta Cosi; Maria Luigia Randi, MD, Prof (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Erythrocytosis is a relatively common condition, however a large proportion of these patients (70%) remain without a clear etiologic explanation.